2021
DOI: 10.1111/asap.12272
|View full text |Cite
|
Sign up to set email alerts
|

Endorsement of stereotypes of older adults, older men, and male leaders predict expected job performance, voting stance, and voting intentions in the 2020 U.S. presidential election

Abstract: The 2020 U.S. Presidential Election offered a unique opportunity to examine how stereotypes of older adults, older men, and male leaders impact expectations of candidate job performance and intentions to vote for Biden or Trump. This online study involved 500 college students from two universities from September 30th until November 3 (Election Day). A Biden model and a Trump model were tested for the relationships among (a) stereotypes from public discourse with (b) expectations of candidates/ presidential per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…The current investigation explored an intervention designed to reduce ageism by combating stereotypes of older adults and did not address intersectional elements of ageism in the content of the intervention nor in the dependent measures. Older adults are not a monolith, and research has increasingly identified that ageism intersects with other ‘isms’ such that there are distinct stereotypes where age (older age) intersects with other group identities (gender, race, sexual orientation, ability status) with distinct consequences for members of those communities (Apriceno & Levy, 2019 ; Chrisler et al., 2016 ; Fredriksen‐Goldsen et al., 2013 ; Laditka et al., 2011 ; Lytle, Apriceno et al., 2018 ; Lytle, Macdonald et al., 2018 ; Monahan et al., 2021 ). A growing body of research demonstrates how older men and women are perceived differently; for example, older women are perceived as being depressed, incompetent, and lonely at earlier ages than men (Hummert et al., 1997 ; Kite & Wagner, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current investigation explored an intervention designed to reduce ageism by combating stereotypes of older adults and did not address intersectional elements of ageism in the content of the intervention nor in the dependent measures. Older adults are not a monolith, and research has increasingly identified that ageism intersects with other ‘isms’ such that there are distinct stereotypes where age (older age) intersects with other group identities (gender, race, sexual orientation, ability status) with distinct consequences for members of those communities (Apriceno & Levy, 2019 ; Chrisler et al., 2016 ; Fredriksen‐Goldsen et al., 2013 ; Laditka et al., 2011 ; Lytle, Apriceno et al., 2018 ; Lytle, Macdonald et al., 2018 ; Monahan et al., 2021 ). A growing body of research demonstrates how older men and women are perceived differently; for example, older women are perceived as being depressed, incompetent, and lonely at earlier ages than men (Hummert et al., 1997 ; Kite & Wagner, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some older adults have faced compounded negative consequences and discrimination based on other stigmatized identities. Scholarly work on the intersections of ageism, ableism, classism, heterosexism, racism, and sexism has been steadily growing (Apriceno & Levy, 2019;Chrisler et al, 2016;Jönson & Taghizadeh Larsson, 2021;Kim & Fredriksen-Goldsen, 2017;Lytle, Macdonald, et al, 2018;Martin et al, 2019;Monahan et al, 2021;Ramírez et al, under review).…”
Section: Psychological and Physical Effects Of Ageism On Older Adultsmentioning
confidence: 99%
“…Indeed, a pressing future direction for interventions is reaching a more diverse population of participants, which is in line with the recurring cross-cutting themes in this article of expanding the circle of study participants and with attention to intersectionality of ageism and other isms (ableism, classism, heterosexism, racism, sexism). Progress is being made in studying a wider range of populations across cultures and contexts (Chrisler et al, 2016;Löckenhoff et al, 2009;North & Fiske, 2015), and some headway in the study of the intersections of ageism with other isms (Apriceno & Levy, 2019;Jarrott et al, 2022;Lytle, Macdonald, et al, 2018;Martin et al, 2019;Monahan et al, 2021;Ramírez et al, under review). Ramírez et al's (under review) systematic review calls attention that ageism reduction interventions need to also educate about the compounding ageism that older adults face and that intergenerational interventions attend to the multiple identities that older adults have.…”
Section: Sub-section Summary and Future Directionsmentioning
confidence: 99%